Odpowiedź :
[tex]\\h=\frac{a\sqrt3}{2}, \ P=\frac{a^2\sqrt3}{4} \\\frac{a\sqrt3}{2}+3=a/*2 \\2a-a\sqrt3=6 \\a(2-\sqrt3)=6/:(2-\sqrt3) \\a=\frac{6}{2-\sqrt3}*\frac{2+\sqrt3}{2+\sqrt3}=12+6\sqrt3 \\P=\frac{(12+6\sqrt3)^2*\sqrt3}{4} \\P=\frac{(144+144\sqrt3+108)*\sqrt3}{4}=63\sqrt3+36*3 \\P=108+63\sqrt3[/tex]
a = ?
P = ?
a - h = 3
a = h + 3
h = a√3/2 ---- wzór na wysokość trójkąta równobocznego
a = a√3/2 + 3 / * 2
2a = a√3 + 6
2a - a√3 = 6
a(2 - √3) = 6
a = 6/(2 - √3)
a = 6(2 + √3) / [(2 - √3)(2 + √3)]
a = 6(2 + √3) / (4 - 3)
a = 6(2 + √3) / 1
a = 6(2 + √3) cm ------ bok trójkąta
P = a²√3/4 ---- wzór na pole
P = [6(2 + √3)]² √3 / 4
P = [36(4 + 4√3 + 3)]* √3 / 4
P = [36√3(7 + 4√3)] / 4
P = 9√3(7 + 4√3)
P = (63√3 + 108 )cm² ---- pole trójkąta